(untitled) - Trần, Thị Anh Đào (Can Tho, 2015)
Impacts of the instructions of predicting and visualizing strategies on EFL learners' reading comprehensionThen given pedagogical implications and recommendations for future research were proposed in teaching and learning EFL reading
Keywords: Enlgish language,Tiếng Anh; Study and teaching,Dạy và học